Facile and diastereoselective arylation of the privileged 1,4-dihydroisoquinolin-3(2H)-one scaffold - Dar’in, Dmitry; Kantin, Grigory; Bunev, Alexander; Krasavin, Mikhail (Beilstein Journal of Organic Chemistry, 2022)
A practically convenient and streamlined protocol for the trans-diastereoselective introduction of an aryl substituent at position 4 of the 1,4-dihydroisoquinol-3-one (1,4-DHIQ) scaffold is presented. The protocol involves direct Regitz diazo transfer onto readily available 3(2H)-isoquinolones followed by TfOH-promoted hydroarylation by an arene molecule. Screening of the novel 1,2,4-trisubstituted 1,4-DHIQs against cancer cell lines confirmed high cytotoxicity of selected analogs, which validates this new chemotype for further investigations as anticancer cytotoxic agents.
Keywords: 1,4-dihydroisoquinol-3-one; heterocyclic diazo compounds; hydroarylation; Regitz diazo transfer; triflic acid